Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/nsmb.3249
|View full text |Cite
|
Sign up to set email alerts
|

Functional interdependence of BRD4 and DOT1L in MLL leukemia

Abstract: Targeted therapies against disruptor of telomeric silencing 1-like (DOT1L) and bromodomain-containing protein 4 (BRD4) are currently being evaluated in clinical trials. However, the mechanisms by which BRD4 and DOT1L regulate leukemogenic transcription programs remain unclear. Using quantitative proteomics, chemoproteomics and biochemical fractionation, we found that native BRD4 and DOT1L exist in separate protein complexes. Genetic disruption or small-molecule inhibition of BRD4 and DOT1L showed marked synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 72 publications
6
93
0
Order By: Relevance
“…Interestingly, spreading targets that overlapped with either broad H3K4me3 or super-enhancers were significantly more sensitive to DOT1L inhibition than spreading MLL-AF4 targets alone (Figure S7D). This indicates that there are further subdivisions of activity within spreading targets themselves, something that may explain recent results looking at DOT1L and BRD4 cooperation (Gilan et al., 2016). …”
Section: Resultssupporting
confidence: 56%
“…Interestingly, spreading targets that overlapped with either broad H3K4me3 or super-enhancers were significantly more sensitive to DOT1L inhibition than spreading MLL-AF4 targets alone (Figure S7D). This indicates that there are further subdivisions of activity within spreading targets themselves, something that may explain recent results looking at DOT1L and BRD4 cooperation (Gilan et al., 2016). …”
Section: Resultssupporting
confidence: 56%
“…While it is not uncommon for variations in stock solution to cause differing compound potency and toxicity (Kannt and Wieland, 2016), a reduced dose could have an impact on I-BET151 efficacy. Indeed, recent work from authors of the original study reported I-BET151 administered at 10 mg/kg had no impact on survival in a MLL-AF9 leukaemia mouse model (Gilan et al, 2016), while I-BET151 administered at 15 mg/kg did provide a survival benefit in a mouse model of NPM1c AML, albeit with a smaller effect size (Dawson et al, 2014).
10.7554/eLife.25306.006Figure 3.Maximal tolerated dose in an I-BET151 treated xenograft mouse model of MLL-fusion leukaemia.Female NOD-SCID mice were conditioned with Busulfan and intravenously injected with 1 × 10 7 MV4;11 cells in vehicle (PBS).
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, evidence indicating potential acquired resistance to BET inhibitors has been reported (Fong et al, 2015; Kumar et al, 2015; Rathert et al, 2015), along with studies which have found that treatment with combinatorial drugs can mitigate acquired resistance (Asangani et al, 2016; Kurimchak et al, 2016; Yao et al, 2015). Furthermore, a recent study reported synergistic effects of combinatorial treatment with a disruptor of telomeric silencing 1-like (DOT1L) inhibitor and I-BET151 in MLL cells and mouse leukaemia models (Gilan et al, 2016). Studies have also addressed the nonclinical safety of BET inhibition and found that BET bromodomain inhibition can impact normal intestinal homeostasis and repair (Nakagawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The same difficulties in establishing causal links apply also in this setting. In that respect exploring metabolic dependencies in settings where a genetic lesion modifies chromatin as in MLL-rearranged leukemias 125, 126 , or pediatric brain tumors and sarcomas with histone mutations 127, 128 , might prove fruitful as these cases could be particularly susceptible to a disruption in metabolism.…”
Section: Future Directionsmentioning
confidence: 99%